Atributos químicos do solo e produtividade da cultura de soja em área de semeadura direta após calagem superficial - Schoninger, Evandro Luiz; Lange, Anderson; Da Silva, Amilton Ferreira; Lemke, Alan Ferraz; Monteiro, Stefan [UNESP]; Da Silva, João Alfredo Neto (Universidade Estadual de Londrina, 2010)
This study was carried out to evaluate the effects of surface application of lime rates on soil chemical attributes and soybean yield in a no-tillage system. It was installed a field experiment in a factorial 2×4, and the factors were: two types of lime (calcitic and dolomitic); four rates (0.0 - 0.5 - 1.0 and 1.5 t ha-1 of CaCO3), in a completely randomized blocks experimental design, with four replications. The experiment was located in Matupá, Mato Grosso State, Brazil, being the work developed between November 2006 and May 2007. The evaluations were chemical attributes in the soil layers (0,0-2,5 cm, 2,5-5,0 cm and 5,0-10,0 cm), and the productive characteristics of soybean. Application of lime increased the soil pH (CaCl 2), the exchangeable Ca and Mg, the effective CEC and the base saturation only in the soil surface layer. The two limes were different only for Ca and Mg values in the first layer of soil, and only for the Mg values in the layer of 2,5-5,0 cm. The surface liming in no-tillage system did not change soybean yield.
Soil chemical atributes and soybean yield in no-tillage system after surface liming
Keywords: Glycine max; Latosol; Lime mobility